Psychological Impact During the First Outbreak of COVID-19 in Italy - Ferrucci, Roberta; Averna, Alberto; Marino, Daniela; Reitano, Maria Rita; Ruggiero, Fabiana; Mameli, Francesca; Dini, Michelangelo; Poletti, Barbara; Barbieri, Sergio; Priori, Alberto; Pravettoni, Gabriella (Frontiers in Psychiatry, 2020)
The first outbreak of COVID-19 in Italy was confirmed on 21 February 2020. Subsequently, COVID-19 turned into a global pandemic, causing a global health emergency, triggering an unprecedented event in the modern era. This study assessed the immediate psychological impact of the COVID-19 epidemic on emotional health and well-being. An ad hoc questionnaire was designed for online completion to expedite data collection during the COVID-19 outbreak. People were invited to participate in the study via social media and email from 4 to 18 March 2020. The entire survey comprised of 21 questions, covering a wide range of factors, such as demographics, disease knowledge, psychological impact, daily life activities, and psychological precautionary measures. The main outcome measure was psychological impact. This was measured based on intensity and prevalence of self-reported feelings of anxiety, fear, sadness, anger, and concern during the epidemic. In total, 10,025 respondents completed the online survey. Of these, about 73% were females, and 100% of the sample possessed good knowledge of the disease. The greatest prevalence of high psychological impact was reported in the <34 years’ age group and in north Italy. Additionally, the psychological impact influenced important daily life activities, such as sexuality and nutrition. Our study provides information about the immediate psychological (emotional feelings) responses of Italy’s general population to the COVID-19 epidemic. The survey covers several factors that can influence mental health; our results help gauge the psychological burden on the community and offer ways to minimise the impact.